Proceedings of the 8th international conference on foundations of computer-aided process design - International Conference on Foundations of Computer-Aided Process Design; Eden, Mario R.; Siirola, John D.; Towler, Gavin P. (Oxford, England Elsevier, 2014)
This volume collects together the presentations at the Eighth International Conference on Foundations of Computer-Aided Process Design, FOCAPD-2014, an event that brings together researchers, educators, and practitioners to identify new challenges and opportunities for process and product design. The chemical industry is currently entering a new phase of rapid evolution. The availability of low-cost feedstocks from natural gas is causing renewed investment in basic chemicals in the OECD, while societal pressures for sustainability and energy security continue to be key drivers in technology development and product selection. This dynamic environment creates opportunities to launch new products and processes and to demonstrate new methodologies for innovation, synthesis and design. FOCAPD-2014 fosters constructive interaction among thought leaders from academia, industry, and government and provides a showcase for the latest research in product and process design.--Provided by publisher.
Electronic reproduction.
Keywords: Civil engineering -- Data processing -- Congresses; Computer-aided engineering -- Congresses; Structural analysis (Engineering) -- Data processing -- Congresses; Electronic books